Problems of Harmonization on The Post-Establishment of Omnibus Law on Job Creation - Henry Lbn Toruan Donald (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
The government has issued Law Number 11 Year 2020 concerning Job Creation (UUCK) on November 2, 2020. Through this law, around 1,200 articles in eighty laws are simplified into one law that regulates the provisions of the replaced laws. The model of simplifying regulations by combining various laws into a law is called the Omnibus Law. The establishment of the UUCK was a form of simplification of regulations related to the job creation process. The statement of the problem of this research is how to harmonize subordinate regulations into law, which was previously an implementing regulation from a law into a law. The research method used is normative juridical which is descriptive analysis. Law No. 12 Year 2011 as amended by Law No. 15 Year 2019 concerning the Establishment of Laws and Regulations states that harmonization was still in the draft stage. Therefore, no provisions govern the harmonization of regulations in force. If there are overlapped regulations both vertically and horizontally under the law, the settlement mechanism is done through the judiciary, namely the Supreme Court. This research concludes that the settlement of the disharmony regulation is resolved through executive review or analysis and evaluation.